Analysis of convergence in transport infrastructure: a global evidence - Saba, Charles Shaaba; Ngepah, Nicholas; Odhiambo, Nicholas Mbaya (European Journal of Transport and Infrastructure Research, 2021)
This study investigates the convergence in transport infrastructure for 102 countries spanning 1990-2018 using Phillips and Sul econometric methodology. We constructed a transportation infrastructure by a composite index of transportation computed via principal component analysis (PCA). Our findings suggest the presence of panel convergence at the global level, while the income groups exhibited panel divergence. The results obtained from the iterative testing procedure suggest that the sub-groups exhibited convergence and divergence features. Overall, this study finds that the process of convergence in transportation reflects the desirable emanations of transportation policies sharing possible similar characteristics, at least to some extent, across the globe.